Mapping the affective turn in education : theory, research, and pedagogies (New York, NY : Routledge, 2020)
Passions are high in education, and this edited volume offers bold new ways to conceive of the affective intensities shaping our present historical moment. Concerns over school practices deemed "ineffective," "disruptive," "irrational," or even "promising" are matters modulated by and through feelings, such as, optimism, shame, enhanced concentration, or empathy. The recent turn to affect offers vibrant methodological and theoretical material for an educational present marked by high stakes rhetoric, heated debate, teacher and student vulnerabilities, and extreme educational measures. Affect studies are a part of new materialist and post-humanist turns, and this volume connects these new theoretical directions within education. This comprehensive volume on affect crosses educational subfields and responds to the transdisciplinary interest in thinking through pedagogy, education, and feeling. This comprehensive reader addresses affect in education from a wide range of styles, topics, and perspectives. This collection offers an introduction to theory, empirical research studies, interviews with affect studies scholars, and an assessment of the current and future significance of affect studies in education. Contributors utilize a range of theoretical and interpretive approaches to thinking with and through schooling phenomena. Interviews with affect scholars in the humanities and social sciences address affective dimensions of teaching. The editors' introduction, different foci, and interdisciplinary genres of writing help readers feel their ways into what affect studies in education does and might do. This field-defining collection will be of interest to a range of readers--from graduate students to established scholars--with varying levels of expertise and familiarity putting affect theories to work in education. All the contributions are accessible to those new to the theory, methods, and debates in this vibrant area of educational studies.
OCLC-licensed vendor bibliographic record.
Keywords: Affective education; Education -- Aims and objectives; Affect (Psychology); EDUCATION / General; EDUCATION / Research; EDUCATION / Philosophy & Social Aspects